PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA MATERI KEBERAGAMAN BUDAYA SISWA KELAS V SD PELANGI MANULAI II - Silviani Gratia Riski Seran; Paulina Riwu Ga; Treesly Y.N Adoe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aim to knowing whether there is a significant influence on student learning results by applying the Make A Match type cooperative learning model in the fifth grade Pancasila Education subject. This study used a type of Pre-Experimental Design research with a quantitative approach One Group Pretest-Posttest Design research design. The population used was grade V students of Pelangi Elementary School, totaling 12 people. The sampling technique used was total sample or saturated sampling. This research instrument is a test in the form of a pretest and posttest to measure learning results. Before using the instrument, the validity and reliability tests were first carried out. After the data is collected, it is then analyzed and used for hypothesis testing. Furthermore, the results of hypothesis testing, using paired sample T-test which shows that the significant value (2-tailed) is 0.001. This shows that the significant level value (2-tailed) <0.05. In accordance with the basis for decision making if the sig value. (2 tailed) <0.05, then there is a significant difference between learning outcomes in pretest-posttest data.Based on the results of the above research, it can be concluded that there is an influence between the Make A Match type model on the learning results of Pancasila Education on the material of cultural diversity of V grade students of Pelangi Manulai II Elementary School.